Danubian Imaginary in the “Book of the Millionaire”: Array - Golovanova, Elena (Journal of Danubian Studies and Research, 2020)
Eugene Ionesco mentioned in 1980 that the person,whom he appreciated and admired, had been one of the best Romanian prose writers of those times and, if Ştefan Bănulescu was not yet known worldwide, the fact was due to the thing that he had been writing in Romanian, a language that had no international circulation. Autarchic imaginary universe, "The Millionaire’s Book", written by Ştefan Bănulescu, is one of the most original spaces of postbelic Romanian prose. From the tetralogy announced by Ştefan Bănulescu under the title "The Millionaire’s Book", only the first volume appeared, "The Book from Metopolis" - a novel of an imaginary territory, which had been designed as a fresco of the Romania of local myths - real and imaginary. "The Book from Metopolis" includes the world of the Danube plain between Călăraşi and Brăila as it was reinvented by the prose writer who knew like no other the great and small history of this piece of country. Ștefan Bănulescu can be subsumed to a Romanian vein of “magical realism”, together with Fănuș Neagu, Dumitru Radu Popescu or Constantin Țoiu. Without necessarily appealing to the fantastic, Șt. Bănulescu builds a universe with fabulous iridescences, fixed in a timeless past. A special light bathes the landscapes and the characters, enveloping them with an aura of story. The objects have a weak but hypnotic inner flicker, and the gestures and actions of the protagonists acquire a kind of hieraticism, of exemplary significance. In Sartre’s terms it could be said that Șt. Bănulescu does not work with perceptions, but with images; the model he has in mind is not the outside world, but an inner world, recreated from fragments of memories, sensations and impressions.